The Use of Beauty Blenders in the Application of Foundation in Adolescents with Combination Facial Skin - Rika Riwayani; Israwati Hamsar (JURNAL PAKARENA, 2023)
This research is a descriptive study that aims to find out, 1) The results of applying foundation using a beauty blender on combination facial skin types and 2) The opinion of the panelists on the results of applying foundation using a beauty blender on combination facial skin types. The number of respondents in this study was 20 trained panelists.Data collection techniques used were observation, Focus Group Discussion (FGD), documentation, questionnaires, and interviews. The data analysis technique used is descriptive and Likert scale. The results of this study indicate 1) Application of foundation using a beauty blender on combination facial skin, evenness is considered even in terms of color but is less able to cover pores and acne scars on the face, the durability of the foundation is considered to be less able to last when left on for 2 hours 2 ) based on the opinion of the panelists regarding the results of applying foundation, the beauty blender is in a good category at a percentage of 65%.